Penilaian Arsip Kesenian di Dewan Kesenian Jakarta - Sekarjati, Amalia; Salim, Tamara Adriani (Khazanah: Jurnal Pengembangan Kearsipan, 2025)
This study aims to identify the archival appraisal process, analyze the value, and interpret the patterns of art archives at the Jakarta Arts Council (DKJ). The selection of informants used purposive sampling technique, namely DKJ members for the 2020-2023 period and staﬀ who have interacted and utilized DKJ  archives. The data collection method was using document analysis, interviews, and observation. It was found that DKJ does not yet have an appraisal instrument such as retention schedule in determining what is kept and disposed. However, during the 2020-2023 period, there was an awareness that the appraisal was carried out for preserving and utilizing the existing archives for their programs, and was dominated by users' perspectives, such as researchers, academics, and curators. Two things are dominant in that appraisal process: the history of DKJ as an art institution, as well as the history, development, and discourse of art, both in Jakarta and Indonesia. This is also reﬂected in the identiﬁcation of the value contained in the existing DKJ archives, including the administrative/operational value of the publication and documentation division as the primary value, as well as the value of the evidence, information, research and reference, historical, and aesthetic and exhibition as secondary values.